Strategi Penyampaian Honorifik dalam Tindak Direktif Larangan Masyarakat Tutur Makassar - Syafruddin Syafruddin (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2010)
Honorific delivery strategy is an integral part of the Indonesian speech act speech of educated families from Makasar speech community. The strategy has a peculiarity. This study was conducted to get an overview and explanation of the delivery of honorific strategy in the speech act of prohibition delivered by educated families from Makasar speech community. This qualitative study uses the pragmatic theory design with ethnography of communication model. The results of this study indicate that the delivery of honorific prohibition strategy embodied in the speech acts of direct and indirect use of honorific alternatives varies with different contexts according to socio-cultural norm they have. Key words: honorific, speech art, Makassar speech community